Genetic Analysis and Pathogenic Characterization of Alternaria tenuissima Induced Fruit Rot of Bitter Gourd - SEHRISH IFTIKHAR; WAHEED ANWAR; Adnan Akhter; SAJID ALI; HAFIZ AZHAR ALI KHAN; MUHAMMAD KHURSHID; MUHAMMAD SALEEM HAIDER (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Iftikhar S, Anwar W, Akhter A, Ali S, Khan HAA, Khurshid M, Haider MS. 2021. Genetic analysis and pathogenic characterization of Alternaria tenuissima induced fruit rot of bitter gourd. Biodiversitas 22: 617-625. Bitter gourd (Momordica charantia Linn.), belongs to Cucurbitaceae family, is widely cultivated in areas with warm climate. In 2017, fruits of bitter gourd-bearing rot symptoms were observed in the Punjab province of Pakistan. The disease-causing fungal isolate was collected from the diseased fruits on potato dextrose agar (PDA). Microscopic examination revealed short conidiophores arose singly, measuring 79.8- 158.5 ?m long and 3.94-7.89 ?m thick. The size of conidia varied from 25.7 to 46.45 ?m and 8.55-14.39 ?m in length and width respectively, which were characteristics of Alternaria spp. To confirm the identity and molecular characterization of the isolate, the internal transcribed spacer (ITS) region, translation elongation factor 1 alpha (TEF1-?), glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and RNA polymerase II large subunit 2 (RPB2) genes were amplified. The sequence analysis of amplicons and phylogenetic studies specified the homology of isolated Alternaria spp. with the previously reported A. tenuissima in GeneBank. The pathogenicity tests conducted on the fruits of bitter gourd confirmed the disease development with typical Alternaria induced rot symptoms, thus satisfied Koch's postulate. To our knowledge, this is the first record of A. tenuissima causing fruit rot of bitter gourd in Pakistan.